Intersectionality of race, ethnicity, class, and gender in teaching and teacher education : movement toward equity in education - Carter, Norvella P.; Vavrus, Michael J. (Advances in teaching and teacher education, 2018)
"In Intersectionality of Race, Ethnicity, Class, and Gender in Teaching and Teacher Education, the editors bring together scholarship that employs an intersectionality methodology to conditions that affect public school children, teachers, and teacher educators. Chapter authors use intersectionality to examine group identities not only for their differences and experiences of oppression, but also for differences within groups that contribute to conflicts among groups. This collection moves beyond single-dimension conceptions that undermines legal thinking, disciplinary knowledge, and social justice. Intersectionality in this collection helps complicate static notions of race, ethnicity, class, and gender in education. Hence, this book stands as an addition to research on educational equity in relation to institutional systems of power and privilege"--